Microarray analysis of isolated human islet transcriptome in type 2 diabetes and the role of the ubiquitin–proteasome system in pancreatic beta cell dysfunction - Bugliani, Marco; Liechti, Robin; Cheon, Hwanju; Suleiman, Mara; Marselli, Lorella; Kirkpatrick, Clare; Filipponi, Franco; Boggi, Ugo; Xenarios, Ioannis; Syed, Farooq; Ladriere, Laurence; Wollheim, Claes; et al. (Molecular and cellular endocrinology, 2013)
► Islets from type 2 diabetic subjects have several transcriptome alterations. ► The ubiquitin–proteasome system (UPS) is deranged in human type 2 diabetic islets. ► Environmental factors can affect islet UPS. To shed light on islet cell molecular phenotype in human type 2 diabetes (T2D), we studied the transcriptome of non-diabetic (ND) and T2D islets to then focus on the ubiquitin–proteasome system (UPS), the major protein degradation pathway. We assessed gene expression, amount of ubiquitinated proteins, proteasome activity, and the effects of proteasome inhibition and prolonged exposure to palmitate. Microarray analysis identified more than one thousand genes differently expressed in T2D islets, involved in many structures and functions, with consistent alterations of the UPS. Quantitative RT-PCR demonstrated downregulation of selected UPS genes in T2D islets and beta cell fractions, with greater ubiquitin accumulation and reduced proteasome activity. Chemically induced reduction of proteasome activity was associated with lower glucose-stimulated insulin secretion, which was partly reproduced by palmitate exposure. These results show the presence of many changes in islet transcriptome in T2D islets and underline the importance of the association between UPS alterations and beta cell dysfunction in human T2D.